DEVELOPMENT OF INTERNATIONAL CRIMINAL JUSTICE - Пименова, Анастасия; Кузьменко, Валентина (SWorldJournal, 2022)
The history of separate institutes of international criminal responsibility is considered in the work, the periods of formation of international cooperation in the field of legal aid in criminal matters in international law from ancient times to the prese